QISHASH SEBAGAI ETIKA KEMANUSIAAN: PEMIKIRAN AL-QUR?UB? DAN RELEVANSINYA BAGI KEPATUHAN SDM DI INDONESIA - Wira Syuhada; Hamdan Ainul Yaqin; Tjatur Sapto Edy; Restu Haji Setiansah (LP2M IAI Muhammadiyah Bima, 2026)
This study examines the thought of Imam al-Qur?ub? on the law of qishash as elaborated in Tafs?r al-J?mi? li A?k?m al-Qur??n, focusing on Q.S. Al-Baqarah: 178-179, and integrates its universal values into modern Human Resource Management (HRM) practice in Indonesia. Using a qualitative library research approach, the study reveals that al-Qur?ub? interprets qishash as a mechanism of justice aimed at preserving life (?if? al-nafs) and social stability. Values of justice, equality, and deterrence (zaw?jir) contained in qishash are significantly relevant for disciplinary policy formulation, proportional sanction systems, and a justice-based compliance culture in HRM. The article concludes that the spirit of Islamic law as explained by al-Qur?ub? provides a strong ethical and philosophical foundation for fair and sustainable HRM practice in Indonesia